Control on judicial discretion of administrative judge - عبود, صعب ناجي; علي, عمار حسين (Journal of Legal Sciences, 2019)
The control over discretion rests with the judgment of the judge who issues it. The court, which is competent to hear the appeal of the judgment, shall examine the judgment and examine it for its validity, including all parts of the sentence and its aspects; The tools that the judge works to reach the conclusion he has reached in the judgment, including. However, the court's control, ie, the court of law, is not absolute. In essence, it does not apply to the legal aspect without the factual aspect, and this does not mean that the court does not consider the factual aspect at all. Rather, it does not mean that the court of law does not take the substance of the truth. By the judge to reach the reality and does not specialize in the original, other than the legal aspect of the provision on which it must do the same effort done by the judge to reach the legal truth contained in the rule, through the realization of mind in the application of the rule or interpretation, if the Court did so and ended To another result, we have reversed.